Confinement by Liquid‐Liquid Interface Replicates In Vivo Neutrophil Deformations and Elicits Bleb‐Based Migration - Jonathan H. Schrope; Adam Horn; Kaitlyn Lazorchak; Clyde W. Tinnen; Jack J Stevens; Mehtab Farooqui; Tanner Robertson; Jiayi Li; David Bennin; Terry Juang; Adeel Ahmed; Chao Li; et al. (Advanced Science)
Abstract Leukocytes forge paths through interstitial spaces by exerting forces to overcome confining mechanical pressures provided by surrounding cells. While such mechanical cues regulate leukocyte motility, engineering an in vitro system that models the deformable cellular environment encountered in vivo has been challenging. Here, microchannels are constructed with a liquid‐liquid interface that exerts confining pressures similar to cells in tissues, and thus, is deformable by cell‐generated forces. Consequently, the balance between migratory cell‐generated and interfacial pressures determines the degree of confinement. Pioneer cells that first contact the interfacial barrier require greater deformation forces to forge a path for migration, and as a result migrate slower than trailing cells. Critically, resistive pressures are tunable by controlling the curvature of the liquid interface, which regulates motility. By granting cells autonomy in determining their confinement, and tuning environmental resistance, interfacial deformations match those of surrounding cells in vivo during interstitial neutrophil migration in a larval zebrafish model. It is discovered that neutrophils employ a bleb‐based mechanism of force generation to deform a soft barrier exerting cell‐scale confining pressures. In all, this work introduces a tunable in vitro material interface that replicates confining pressures applied by soft tissue environments.